2011
DOI: 10.3390/ijerph8062132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Discontinuation of Fluoride Intake from Water and Toothpaste on Urinary Excretion in Young Children

Abstract: As there is no homeostatic mechanism for maintaining circulating fluoride (F) in the human body, the concentration may decrease and increase again when intake is interrupted and re-started. The present study prospectively evaluated this process in children exposed to F intake from water and toothpaste, using F in urine as a biomarker. Eleven children from Ibiá, Brazil (with sub-optimally fluoridated water supply) aged two to four years who regularly used fluoridated toothpaste (1,100 ppm F) took part in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In the present pilot study, the length of time for a ‘wash-out’ period was determined based on the previous studies in children and adults which have reported a rapid decrease in circulating F in the body of young children in the first 24 hours after discontinuation of F from water and toothpaste 28 , in contrast to a relatively constant UFE in adults being reached in one week following fluoridation of water 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present pilot study, the length of time for a ‘wash-out’ period was determined based on the previous studies in children and adults which have reported a rapid decrease in circulating F in the body of young children in the first 24 hours after discontinuation of F from water and toothpaste 28 , in contrast to a relatively constant UFE in adults being reached in one week following fluoridation of water 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is evident that the analysis of fluoride in body fluids besides drinking water is highly relevant and necessary for understanding potential health implications (Martins et al 2011). The results of the present investigation indicate that improvement in the health of the children would likely be achieved if management strategies incorporate emerging knowledge to address fluoride toxicity in the individuals, even if residing in non endemic fluoride areas.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide age range of participants of the included studies, studies were grouped into three groups according to the age of the participants; 2–5 years (17 studies) [ 26 , 28 , 36 , 43 – 45 , 50 , 51 , 54 57 , 60 , 62 , 68 , 72 , 74 , 75 ], 6–12 years (20 studies) [ 25 , 30 , 35 , 36 , 45 48 , 52 , 54 , 58 , 59 , 61 , 63 66 , 71 , 76 , 81 ] and 13 to < 19 years (12 studies) [ 25 , 26 , 29 , 36 , 49 , 53 , 54 , 63 , 65 , 67 , 69 , 81 ]. These cut-points were chosen based on the WHO criteria for assessing population iodine deficiency, which defines school-aged children as between 6 and 12 years of age [ 6 ].…”
Section: Methodsmentioning
confidence: 99%